THE INTERTEXTUALITY OF CULTURAL REPRESENTATIONS AS SEEN FROM SPIDERMAN ACROSS THE SPIDER-VERSE (2023) AND MS MARVEL (2022) - Sekarini, Siska Ayu Diaz; Khadija Albar Hanafi; Isna Shofiyani Fathoni (UIN Raden Mas Said Surakarta, 2024)
This study aims to reveal the intertextual of cultural diversity of Spiderman Across the Spider-Verse (2023) and Ms. Marvel (2022). This study focuses on Spiderman characters: Miles Morales and Pavitr Prabhakar and also Ms. Marvel named Kamala in Ms. Marvel, social life and their surroundings. This study uses the theory from Kristeva (1989) to examine the intertextuality between the two films and representative theory from Stuart Hall(1997) to analyze the cultural representation of Spiderman Miles Morales, Spiderman Pavitr Prabhakar, and Kamala Khan. The researchers used qualitative research methods. Research results show that cultural representation in movies appears beyond superficial markers, incorporating meaning, signs and symbols that are relevant to the characters' backgrounds in society. Both films depict elements such as food, stereotypes, and religious norms that represent a specific culture or religion. However, both films clearly reflect traditional fashion symbols, musical instruments, language, traditions, decorations, and religious rituals. This intertextual exploration enriches the story and offers a more inclusive depiction of superheroes in a globalized worldThis study is expected to provide insightful and nuanced understandings of cultural representation in this modern era of globalization through the eyes of Spiderman Across the Spider-Verse (2023) and Ms. Marvel (2022).